2018
DOI: 10.1097/pq9.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Intervention to Decrease Hypothermia in the Delivery Room Using a Checklist

Abstract: Introduction: Premature babies are at increased risk of hypothermia, core body temperature <97°F. Delivery room environment may contribute and lead to complications. The objective was to reduce hypothermia in babies <32 weeks of gestation in the delivery room to <40% using a checklist and sustain it for 6 months. Methods: We created a delivery room checklist in 2012. Chart review established a baseline rate of hypothermia (<97°F). The team analyzed the checklist’s effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Multiple reports describe efforts by single NICUs and collaboratives to reduce hypothermia through structured QI methods 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 . Outcome measures primarily examined temperature on NICU admission, with some reports also examining other morbidities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple reports describe efforts by single NICUs and collaboratives to reduce hypothermia through structured QI methods 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 . Outcome measures primarily examined temperature on NICU admission, with some reports also examining other morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Other interventions included pre-delivery team preparation, staff education, improved storage of necessary equipment near point of care, having a dedicated OR for all preterm deliveries, measuring infant's temperature during DR stabilization, and having staff designated to temperature control. Approaches to improvement and standardization included checklists, guidelines, or thermoregulatory bundles 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 . Some centers used a stepwise approach to implement these same interventions 10 , 11 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…23 In addition, applying checklists at the time of delivery can have important clinical repercussions such as the reduction of hypothermia in newborns after birth. 24,25 Therefore, we believe that these lists should be used routinely in the preparation of materials for members of the resuscitation team before CPR. Indeed, in our work, 11.5% of minor rectifiable defects were detected by performing a systematic check, like those provided on the checklist, prior to carrying Abbreviations: FiO 2 , inspired oxygen fraction; PEEP, positive end expiratory pressure; PIP, maximum inspiration pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Checklists have been used successfully in the delivery room to decrease hypothermic temperatures for premature infants being admitted to the NICU. 14 Engorn et al 15 showed that the use of a checklist helped reduce postoperative hypothermia in NICU patients. Furthermore, the Children’s Hospitals Neonatal Consortium STEPP-IN initiative published results showing that a multi-institutional quality improvement project reduced postoperative hypothermia from 20.3% to 10.5%.…”
Section: Introductionmentioning
confidence: 99%